Pelaksanaan Peraturan Menteri ESDM No21 Tahun 2017 - Fatmah, Fatmah; Dalimunthe, Dermina (Jurnal El-Thawalib, 2021)
This study discusses the implementation of the Minister of Energy and Mineral Resources Regulation No. 21 of 2017 Article 3 Paragraph (1) concerning the Management of Drill Mud and Drill Cutting Waste in Geothermal Drilling by the Mandailing Natal Regency Environmental Service. This research was motivated by complaints from residents of the village of Sibanggor Tonga, Puncak Sorik Marapi District, Mandailing Natal Regency about the waste flowing into the residents' agricultural land which resulted in the residents' rice plants not developing as usual, causing implementation that was not in accordance with existing regulations.  This type of research is afield researchusing a qualitative descriptive analysis method. The method of collecting data for this research is by means of interviews and documentation in accordance with the provisions contained in the Regulation of the Minister of Energy and Mineral Resources Number 21 of 2017.  The results of the study state that the implementation of the Minister of Energy and Mineral Resources Regulation Number 21 of 2017 Article 3 Paragraph (1) concerning the Management of Drill Mud and Drill Cutting Waste in Geothermal Drilling by the Mandailing Natal Regency Environmental Service has been implemented, this can be seen from the form of implementation that has been implemented by The Environment Agency is to carry out direct supervision of the location of the flow of waste, give warnings to geothermal energy companies if they have violated the provisions in the regulations and impose sanctions on the agency or company if they have violated applicable regulations or are not in accordance with the company's way of working.